METHOD FOR PRODUCING A FIRE RETARDANT AGENT WITH NITRIC ACID SOLUTIONS OF VARIOUS CONCENTRATIONS - Muratova, Manzura (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The purpose of this work is to study the content of nitrate ions in the manifestation of the fire retardant effectiveness of the product of nitric acid processing of low-grade phosphorites for the fire protection of cellulose materials. To achieve the goal of this study, a method was used to study the features of the processes of processing low-grade phosphorites with solutions of nitric acid in various concentrations. To study the effect of concentration (СHNO3 = 5, 10, 20 %) on the solubility of samples (dust fraction (DF)), phosphorite layer-1 (FL1), phosphorite layer -2 (FL2), mineral mass (ММ) low-grade phosphorites and extraction of main flame retardant components Σfire retardant component experimental studies were carried out in the liquid phase. The following methods were used in the research process: chemical elemental analysis, microprobe analysis, infrared spectroscopy, potentiometry, viscometry, special methods for determining the flammability and fire protection of materials.